Faites le buzz ! Un vieux mécanisme rhétorique adapté à l’espace médiatique contemporain ? - Collinet, Françoise (Studia Romanica Posnaniensia, 2017)
Presidential elections, by their nature, provoke fierce debates. During the 2017 French campaign the heated exchange between C. Angot and F. Fillon attracted public attention: that “clash” was making a “buzz”. Our attention was first caught by the terminology recurrently used by the media: in which ways are “clashes” and “buzzes” different from but also similar to old rhetorical mechanisms? And, more specifically, would New Rhetoric’s sensitivity to historical relativity shed some light on the issue? At first, we assumed that, polemic being a typical argumentative situation, there was no incompatibility between that theoretical framework and the study of a concrete polemical exchange. Of course, New Rhetoric doesn’t focus on polemical exchanges; we do, however, share Nicolas’ unease at saying that Perelman idealizes philosophical agreement (e.g. Nicolas, 2015a, § 7). After addressing that issue and the ambivalence of Perelman’s position, we will say a few words about the end / consequence distinction.